Reducing the Burden of Mortality in Older People With Diabetes: A Review of Current Research - Forbes, Angus (Frontiers in Endocrinology, 2020)
This review considers the burden of mortality observed in the older population of people with diabetes and identifies the risk factors associated with mortality hazard in this population. The mortality gap between older people with and without diabetes is enduring, with excess mortality being 10% greater than in the general population. While early mortality in men with diabetes is significantly greater than females with diabetes, the relative mortality risk in females is much higher compared to women without diabetes. Older people who have developed diabetes in middle age have significantly higher mortality hazard compared to those who develop it in old age, emphasising the continued importance of optimising diabetes care in all ages. To minimise mortality hazard in older age it is important to address some of the factors that convey risk, these include: comorbidity; polypharmacy; physical and mental frailty; safe glycaemic targets for older people; hypoglycaemia; glycaemic targets; and the hypoglycaemic agents. While the data to determine optimal management approaches are limited, the overall need is for a more diligent approach in assessing the needs of older people with diabetes to inform individualised care strategies and therapy goals that minimise potential hazards.